2019
DOI: 10.3389/fpubh.2019.00268
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Recommended Vaccines and Its Associated Factors Among Malaysian Pilgrims During Hajj and Umrah 2018

Abstract: This study aimed to assess the uptake of recommended vaccines and to identify the factors associated with the vaccines' uptake among Malaysian Hajj and Umrah pilgrims. A cross-sectional survey among Malaysian Hajj and Umrah pilgrims in 2018. The uptake of the recommended vaccines was surveyed through an anonymous self-administered questionnaire to pilgrims attending a pre-departure Hajj/Umrah orientation course. Descriptive statistics were used for elaborating the demographic characteristics and vaccines uptak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 35 publications
(39 reference statements)
0
15
0
Order By: Relevance
“…Although our results cannot be generalized to all pilgrims, this study is the first of its kind to assess pilgrims’ KAP continuously throughout the Hajj journey to understand their health behaviors, experience of using preventative measures and the development of acute respiratory infections, and other symptoms of infections. In the meantime, studies conducted in France and Malaysia have shown that compliance to some preventive measures such as hand hygiene and face mask use has increased, while the uptake of recommended vaccines including influenza and pneumococcal vaccines still remains low [ 36 , 37 , 38 ]; therefore, awareness campaigns should be continued to tackle respiratory infections including the ongoing COVID-19 pandemic that, thus far, has taken a toll of over 200,000 people across the world (as of 27 April 2020) and affected many Muslim countries including Saudi Arabia [ 39 ]. To mitigate the epidemic, the Saudi Arabian authority has already temporarily cancelled Umrah (minor pilgrimage) visit to Makkah [ 40 ]; the decision on whether this year’s Hajj pilgrimage (late July to early August) should be cancelled or not remains to be decided and may depend on the progress of the pandemic [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although our results cannot be generalized to all pilgrims, this study is the first of its kind to assess pilgrims’ KAP continuously throughout the Hajj journey to understand their health behaviors, experience of using preventative measures and the development of acute respiratory infections, and other symptoms of infections. In the meantime, studies conducted in France and Malaysia have shown that compliance to some preventive measures such as hand hygiene and face mask use has increased, while the uptake of recommended vaccines including influenza and pneumococcal vaccines still remains low [ 36 , 37 , 38 ]; therefore, awareness campaigns should be continued to tackle respiratory infections including the ongoing COVID-19 pandemic that, thus far, has taken a toll of over 200,000 people across the world (as of 27 April 2020) and affected many Muslim countries including Saudi Arabia [ 39 ]. To mitigate the epidemic, the Saudi Arabian authority has already temporarily cancelled Umrah (minor pilgrimage) visit to Makkah [ 40 ]; the decision on whether this year’s Hajj pilgrimage (late July to early August) should be cancelled or not remains to be decided and may depend on the progress of the pandemic [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study was carried out among Malaysian Umrah pilgrims attending a weekly Umrah orientation course organized by private Umrah tour companies from March to June 2018. This study was the second stage of a large study [ 24 26 ]. In the first stage, we conducted an exploratory factor analysis of the measurement tool [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, none of the health educational intervention was based on any health behaviour theory to boost compliance with these preventive practices and increase their levels of knowledge towards respiratory tract infection, preventive attitudes and practices towards prevention strategies. Similarly, there is also low compliance with the preventive measures among Malaysian pilgrims [7,17]. Therefore, the objective of this study is to develop and evaluate the impact of health education intervention in reducing the incidence of ILI among Hajj pilgrims from Malaysia.…”
Section: Some Studies Have Been Conducted On Educational Interventionmentioning
confidence: 99%